The role of platelets in defence against pathogens - Clemetson, K. J. (Hämostaseologie, 2011)
Many more platelets are present in healthy mammals than are necessary for routine haemostasis. Thus, they could have other functions. Platelets have many of the attributes of innate immune function including Toll-like receptors. They also contain a wide range of anti-microbial peptides in storage granules. Platelets play an important role in bacterial infections, both in disease progress and in defence mechanisms depending on circumstances. Similar mechanisms are used in defence against fungi. Platelets are also involved in viral diseases, either in protecting from the immune system or in killing viruses that activate platelets. Finally, platelets have a role in defence against parasitic diseases, in particular malaria, that should not be ignored, and may aggravate some of the worst aspects. Platelets also have receptors for IgE and are implicated via parasitic disorders in development and problems of allergy.
Keywords: Platelets; haemostasis; immunology; bacteria; fungi; viruses; parasites; allergies